THE INFLUENCE OF PERSONAL ATTITUDE, SUBJECTIVE NORM AND PERCEIVED BEHAVIORAL CONTROL ON ENTERPRENEURIAL INTENTION (A Study on Students of Management Department, Faculty of Economic and Business, Brawijaya University). - PUTRA, YAN CAHYA PERMANA (Jurnal Ilmiah Mahasiswa FEB, 2018)
The purpose of this research is to analyze factors that influence the entrepreneurial intention of students of managementdepartment in the Faculty of Economics and Business of Brawijaya University using the Theory of Planned behavior consisting of personal attitude, subjective norm, and perceived behavioral control.Eighty-nine students of class of 2015, 2016, and 2017 were selected as respondents using simple random sampling. The data were collected through questionnaires and analyzed using multiple linear regression, preceded by validity test, reliability test, and classical assumption test in SPSS. The result of this research indicates that personal attitude, subjective norm, and perceived behavioral control partially and simultaneously have a significant effect on entrepreneurialintention,where subjective norm is the most dominant variable.Keywords: personal attitude, subjective norm, perceived behavioral control, entrepreneurialintention